2019
DOI: 10.1186/s12913-019-4393-6
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete recording of Indigenous identification status under-estimates the prevalence of Indigenous population attending Australian general practices: a cross sectional study

Abstract: Background Australian Aboriginal and Torres Strait Islander (Indigenous) peoples face major health disadvantage across many conditions. Recording of patients’ Indigenous status in general practice records supports equitable delivery of effective clinical services. National policy and accreditation standards mandate recording of Indigenous status in patient records, however for a large proportion of general practice patient records it remains incomplete. We assessed the completeness of Indigenous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Finally, those organising appointments, conducting dental examinations and collecting chairside data are almost always non-indigenous, which makes many participants who identify as indigenous feel anxious, judged and devalued. For reasons relating to past experiences of discrimination and stigma, many opt not to identify as indigenous [ 35 ]. Numerator-denominator bias …”
Section: Main Textmentioning
confidence: 99%
“…Finally, those organising appointments, conducting dental examinations and collecting chairside data are almost always non-indigenous, which makes many participants who identify as indigenous feel anxious, judged and devalued. For reasons relating to past experiences of discrimination and stigma, many opt not to identify as indigenous [ 35 ]. Numerator-denominator bias …”
Section: Main Textmentioning
confidence: 99%
“… 22 , 30 Research has found that many health care practitioners in Australia do not systematically collect Indigenous identity information. 28 , 33 A study of Indigenous identity collection in primary care settings in Australia found that higher rates of identifier recording were often associated with older patient age, practices outside of a major city, and patients who were long-time clients of a practice. Patients of larger primary care practices and were younger in age were less likely to have an identifier recorded.…”
Section: Resultsmentioning
confidence: 99%
“…For example, despite Australia having an Indigenous identifier mandated by law, the identifier is still not systematically collected across health care sites and Indigenous people are frequently under-identified. 22 , 28 Under-identification can also be attributed to the general distrust of health care settings among Indigenous people. Cultural safety within health care settings could be enhanced through health care partnerships with Indigenous organizations and nations, requiring a representative workforce in all positions in health care settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of data also limits what we know about diagnosis and treatment outcomes via cancer registry data. Problems with data quality include issues with misidentification and underidentification of Aboriginal and Torres Strait Islander peoples in general administrative datasets and cancer-specific datasets,12 13 and a lack of national data on screening programmes 14. In more recent times cancer has become recognised as one of the leading contributors to the burden of disease for Aboriginal and Torres Strait Islander peoples 15…”
Section: Introductionmentioning
confidence: 99%